(3JhVjM GdJPcQI GdWhSjIs - (3Gdbej GdfjSGHhQj, fXGe GdOjf, GdCYQL, GdfXGe GdfjSGHhQj, GdMSf Hf eMeO Hf GdMSjf, J HYO (B850(3g` (B1446(3es
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg GdPj LYdfG ef GdeJacQjf aj Ndb GdCQV hGdSehGJ (B... (3hEf cJGH GdJPcQI (B.... (3bGd GdeUfa(B: (3fQjO Cf fhQO LedG ef Yde GdgjFI(B...s
(3BNQgG (B:s
(3BNQgG(B: (3hdSJ Cbhd eG Gbhd GSJcHGkQG hGaJNGkQG hEfeG GdZQV MK GdWGdH Ydi GdMb Cf jRhQ Yfg CRhQGQG aGdMb CMb Cf jJHY hGdUOb Mbjb HCf jSeY RGOfG Gddg JYGdi hEjGce QZHI aj GdMb GdUQjM hGdbhd GdUMjM hLYd eG dbjJ aj JhVjM gPG GdcJGH ef YQb GdLHjfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B2: 216s
(3GdPQjYI, L (B4: 357s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJfLjes